1997
DOI: 10.1177/026119299702500108
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of 20 Chemicals from the MEIC Programme Determined by Growth Inhibition of L-929 Fibroblast-like Cells

Abstract: The Multicentre Evaluation of In vitro Cytotoxicity (MEIC) programme is an international project aimed at evaluating the relevance of in vitro tests in predicting human toxicity. We have screened 20 chemicals (MEIC codes 31-50) from the programme, by using a cytotoxicity test based on growth inhibition of the mouse fibroblast-like L-929 cell line. Inhibition of cell growth was determined by the neutral red uptake method, which is well established and is used for screening the cytotoxicity of chemicals and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…To date, very few experiments have been performed with fibroblast cells to test the wound-healing activity of drugs, although fibroblast cells have been widely used in a variety of biological tests; for example, studies for anti-ageing activity (34-37), toxicity testing (38,39) and free-radical activity (40). A previous study has shown that pantothenic acid formed by the metabolism of dexpanthenol increases the mitotic activity of cultured human fibroblasts (41).…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few experiments have been performed with fibroblast cells to test the wound-healing activity of drugs, although fibroblast cells have been widely used in a variety of biological tests; for example, studies for anti-ageing activity (34-37), toxicity testing (38,39) and free-radical activity (40). A previous study has shown that pantothenic acid formed by the metabolism of dexpanthenol increases the mitotic activity of cultured human fibroblasts (41).…”
Section: Discussionmentioning
confidence: 99%